2016
DOI: 10.5935/1678-4669.20160035
|View full text |Cite
|
Sign up to set email alerts
|

Eccentricity dimension of the Dimensional Clinical Personality Inventory: Review and psychometric properties

Abstract: We aimed to review of the Eccentricity dimension of the Dimensional Clinical Personality Inventory (IDCP), through two steps.The first one focused on developing new items and the second on testing the psychometric properties in a sample of 225 subjects (70.1% females), aging between 18 and 66 years, mostly undergraduate students (58.9%). The subjects answered the IDCP, and the Brazilian versions of the NEO-PI-R, PID-5 and MIS. The first step resulted in 42 items, which 22 were new. The ResumenDimensión Excent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This pattern, only observed in the models considering several traits at the same time (but not observed in one by one correlations), can occur as an effect related to the measurement of pathological traits, mainly Conscientiousness and Attention Seeking, as discussed previously in literature (Carvalho, Pianowski, Silveira, Bacciotti, & Vieira, 2016;Carvalho, Souza, & Primi, 2014). Indeed, these pathological traits tend to seem less impaired in comparison to other pathological traits.…”
Section: Discussionsupporting
confidence: 47%
“…This pattern, only observed in the models considering several traits at the same time (but not observed in one by one correlations), can occur as an effect related to the measurement of pathological traits, mainly Conscientiousness and Attention Seeking, as discussed previously in literature (Carvalho, Pianowski, Silveira, Bacciotti, & Vieira, 2016;Carvalho, Souza, & Primi, 2014). Indeed, these pathological traits tend to seem less impaired in comparison to other pathological traits.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, according to the hypotheses, we administered the following factors: self-devaluation (7 items), abandonment avoidance (6 items), vulnerability of the scale were previously investigated. [27][28][29][30][31][32][33] Internal consistency reliability in the present study was > 0.70 for almost all factors, except for emotional inexpressiveness factor (0.65) and deceitfulness of others (0.67).…”
Section: Dimensional Clinical Personality Inventory 2 (Idcp-2)mentioning
confidence: 70%
“…The idcp-2 is composed of 206 items distributed in 12 dimensions, with a 4-point Likert-type response scale (1 = "has nothing to do with me" and 4 = "has a lot to do with me"). Previous studies indicated the validity of idcp-2 factors (e.g., Carvalho, Pianowski & Miguel, 2015;Carvalho, Pianowski, Silveira, Bacciotti & Vieira, 2016;Carvalho, Sette & Ferrari, 2016).…”
Section: Methodsmentioning
confidence: 99%